2005
DOI: 10.1016/j.orthres.2005.03.011.1100230608
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional computed tomography of the hip in the assessment of femoroacetabular impingement

Abstract: Femoroacetabular impingement secondary to the cam effect is thought to be associated with an insufficient anterior concavity in the sagittallaxial plane of the femoral head-neck junction. Using three-dimensional computed tomography the anterior and posterior concavity of the femoral head-neck junction was assessed in 36 painful non-dysplastic hips (30 patients). The mean age of the symptomatic hips was 40.7 with 13 females and 17 males. Eighteen out of the 36 hips had a pistol grip deformity. Magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(61 citation statements)
references
References 39 publications
3
54
0
4
Order By: Relevance
“…The definition of a pathologic alpha angle varies across the literature [1,3,6,19], but on review of all definitions, prevalence in the general populations has been reported 14-17% [11,12]. Our series demonstrated a 46% prevalence of abnormal alpha angle in 31B fractures with a 63% prevalence in type the 31B3 subgroup.…”
Section: Discussionmentioning
confidence: 62%
“…The definition of a pathologic alpha angle varies across the literature [1,3,6,19], but on review of all definitions, prevalence in the general populations has been reported 14-17% [11,12]. Our series demonstrated a 46% prevalence of abnormal alpha angle in 31B fractures with a 63% prevalence in type the 31B3 subgroup.…”
Section: Discussionmentioning
confidence: 62%
“…Consensus is required on the threshold values with regard to what is normal and abnormal in all of the imaging modalities. For example, the threshold value of the AA has been suggested to be 50°based on the MRI (21), and 55°based on the CT (22). However, the reliability of its measurement and reproducibility have been questioned (23).…”
Section: Discussionmentioning
confidence: 99%
“…This could enhance understanding of the underlying hip disease in a patient and sensitize the treating physician so that he or she could recognize the importance of subtle deformities. Other imaging modalities (eg, bone scintigraphy [ 43 ]) have not yet been fully evaluated.…”
Section: Discussionmentioning
confidence: 99%